The Spirit and Democracy: Base Communities, Protestantism, and Democratization in Latin America - Smith, Christian (Sociology of religion, 1994)
This article evaluates the impact of Latin American base ecclesial communities (CEBs) and Protestantism on the consolidation of democracy in Latin America, with special emphasis on their role in transforming the dominant political culture of monistic corporatism. The article suggests that in the short run CEBs represent a significant force helping to strengthen democracy in Latin America, while Latin American Protestantism, for the most part, does not. It also suggests, however, that in the long run CEBs may increasingly encounter limitations in their ability to contribute to the strengthening of democracy, while in contrast, Latin American Protestantism is likely to emerge as a significant positive force helping to foster democratization.